(untitled) - Thomas, Jodi; Copyright Paperback Collection (Library of Congress) (New York, 2008)
Allie has always thought that only bad luck came her way. When she inherits the Twisted Creek cafâe, at first she is waiting for the next calamity to occur, but gradually she meets the local people and realizes that she has finally found a safe haven.
Keywords: Fiction; Restaurants; Fiction; Single women; Texas; Fiction; Love stories